2020
DOI: 10.1093/advances/nmz084
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation and Body Weight: A Systematic Review and Dose–Response Meta-analysis of Randomized Controlled Trials

Abstract: The aim of this study was to determine the effect of zinc supplementation on anthropometric measures. In this systematic review and dose–response meta-analysis, we searched PubMed, Scopus, ISI Web of Science, and the Cochrane Library from database inception to August 2018 for relevant randomized controlled trials. Mean differences and SDs for each outcome were pooled using a random-effects model. Furthermore, a dose–response analysis for zinc dosage was performed using a fractional polynomial model. Quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 82 publications
3
20
3
4
Order By: Relevance
“…We have to identify optimal candidates and duration of zinc supplementation for the renal anemia management. A recent meta‐analysis reported that zinc supplementation increased body weight and/or BMI in MHD patients . However, GNRI, which is nutritional indicator and comprises BMI, did not significantly change in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We have to identify optimal candidates and duration of zinc supplementation for the renal anemia management. A recent meta‐analysis reported that zinc supplementation increased body weight and/or BMI in MHD patients . However, GNRI, which is nutritional indicator and comprises BMI, did not significantly change in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…A recent meta-analysis reported that zinc supplementation increased body weight and/or BMI in MHD patients. 23 However, GNRI, which is nutritional indicator and comprises BMI, did not significantly change in this study. Mechanisms and clinical implications of increasing BMI in zinc supplementation for MHD patients remain unclear.…”
Section: F I G U R Econtrasting
confidence: 59%
“…A cutoff BMI of 20 is recommended for diagnosis of protein energy wasting in Japanese patients on HD [38], suggesting that lower BMI is associated with mortality, especially in elderly patients on dialysis. It has also been reported that zinc supplementation might improve appetite, stimulate food intake, and increase BMI in patients on HD and that the serum leptin level is decreased in the HD population [39][40][41]. Furthermore, zinc supplementation was shown to increase the total cholesterol level and rate of protein catabolism in patients on HD [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the IG, independent of the decrease in total energy intake, the significant increase of serum zinc levels led to a reduction of inflammation and consequently weight loss [ 41 ]. A meta-analysis showed no significant changes in anthropometric measures after zinc supplementation (ranged from 4 to 48 week, in different disease) in the overall analysis [ 42 ]. According to previous study, insufficient data about the effect of zinc supplementation on anthropometric indices in migraine patients has been reported [ 42 ], that needs to be evaluated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed no significant changes in anthropometric measures after zinc supplementation (ranged from 4 to 48 week, in different disease) in the overall analysis [ 42 ]. According to previous study, insufficient data about the effect of zinc supplementation on anthropometric indices in migraine patients has been reported [ 42 ], that needs to be evaluated in the future studies. Among possible mechanisms involved in weight loss following zinc supplementation can be mentioned the role of zinc in regulating appetite by altering the metabolism of hypothalamic neurotransmitters and increasing leptin secretion, inhibiting gene mutations leading to obesity, improving insulin sensitivity and reduction of inflammation [ 41 43 44 45 ].…”
Section: Discussionmentioning
confidence: 99%